A non-specific biomarker of disease activity in HIV/AIDS patients from resource-limited environments - Bipath, Priyesh (Afr Health Sci, 2015)
BACKGROUND: A general non-specific marker of disease activity that could alert the clinician and prompt further investigation would be of value in patients with HIV/AIDS, especially in resource limited environments. OBJECTIVE: To investigate the potential of neopterin as non-specific biomarker in patients with advanced HIV/AIDS. METHODS: Cross-sectional study in 105 HIV positive patients (75 on highly active antiretroviral treatment (HAART). Neopterin was assessed by enzyme linked immune-absorbent assay and cytokines by flow cytometry. RESULTS: Neopterin levels were significantly higher (p<0.001) for the total patient than for the control group. Significant correlations between neopterin and plasma indicators of inflammation showed neopterin to be a good indicator of active inflammatory status and of the effect of HAART on the immune system. Neopterin was superior to C-reactive protein and to individual cytokines as indicator of immune deficiency. Increased neopterin levels were associated with a decline in albumin, haemoglobin and the albumin/globulin ratio, and with increases in red cell distribution width. CONCLUSIONS: Plasma neopterin is a good non-specific biomarker of disease activity in HIV/AIDS patients. It is a good indicator of inflammatory activity, perpetuation of inflammation-associated co-morbidities, degree of immune deficiency and has predictive value for underlying disease, and for monitoring the HAART response.